Time, space, and motion in the age of Shakespeare - Fletcher, Angus, 1930-2016 (Harvard University Press, 2007)
Taking us to the very heart of the enterprise of the Renaissance, this closely focused but far-reaching text reveals how early modern science and English poetry were in many ways components of one process: discovering and expressing the secrets of motion, whether in the language of mathematics or verse.